PLANT-EXTRACT-ASSISTED GREEN SYNTHESIS OF SILVER NANOPARTICLES AND THEIR IMPORTANCE - Dr. Sangeeta Gautam (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2015)
The present paper briefly describes the biosynthesis of silver nanoparticles and their application in different fields. Biosynthesis is a novel way to synthesize nanoparticles by using biological sources. It is gaining much attention due to its cost effective, eco friendly and large scale production possibilities. Generally physical, mechanical and chemical methods are involved for the synthesis of such important nanoparticles. But these methods are very expensive and some methods involve harmful chemicals. With the aim of developing clean, nontoxic and eco-friendly technologies, a wide range of biological sources has been used for the formation of nanoparticles. The importance of this study includes a precise and specific analysis of silver nanoparticles from biological systems that may support and revolutionize the art of synthesis. Nanotechnology is a modern field of science which plays a significant role in day to day life aspects. Keywords: Green Synthesis, Nanoparticles, Plants.